PERCEPTION OF HIV STIGMA PERCEPTION IN HIV INFECTED PEOPLE - Rini - Anggraeni; Titin Sutini; Sukma Senjaya (Journal of Maternity Care and Reproductive Health, 2020)
HIV (Human Immunodeficiency Virus) is a virus that can attack the human immune system. In Garut infected with HIV during 2018 there were 251 and the number who died was 181, also the cause of high mortality and morbidity, which can cause psychosocial problems such as stigma. The purpose of this study to describe the perception of HIV stigma in Guntur Garut Army Hospital. The design of this study was descriptive quantitative with a population of people infected with HIV of 199 people. The sample collection technique used Accidental Sampling with a sample size of 45, the variable in this study was HIV stigma. The questionnaire used is the Berger stigma scale, with the results of the validity test of 0.98 and Cronbach's alpha reliability of 0.92. Using Univariate Analysis Techniques. Based on the results of the study, it can be seen that 57.8% of respondents have a bad HIV stigma, when viewed from several dimensions, the highest dimension is Disclosure Cocerns 55.6%. Then Public Attitude 53.3%, Personalized Stigma dimensions 68.9%, and Negative Self Image dimensions 64.4% B. Results. Conclusion Based on the results of research conducted on 45 respondents, it was found that the perception of HIV stigma at the TNI AD Guntur Garut Hospital had a bad stigma perception. In the Disclosure Cocerens dimension, it was the highest aspect that was perceived as lacking, followed by public attitudes, Personalized Stigma and Negative Self Image.